(untitled) (Innovative professional education, 2025)
Based on practical skills in teaching professional subjects, as well as analysis of sources on diversifying lesson material, certain recommendations have been formed for conducting consultations on entrepreneurship, as well as professional orientation for students of vocational (vocational) education institutions. Recommendations for conducting lessons of general professional subjects are described. Examples of practical classes are given